Pesquisa da síntese dos referenciais teóricos na formação contínua de professores dos anos iniciais no campo conceitual multiplicativo - Souza de Alencar, Edvonete (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article present an excerpt from a doctoral thes is in progress, developed in the Graduate Program in Mathematics Education at the Pontifical Catholic University of São Paulo Program. The aim four study is to perform syntheses of themos t used theoretical frameworks in dissertation sand the se son Brazilian continuing education for teachers of the early years in the multiplicative conceptual field. However our goal in this article is to present the development to fre search and its initial data. The methodology used in this study is documental-qualitative meta-synthesis, in which the data collection was carried out in search of dissertation sand theses platform: National Digital Library of These sand Dissertation sand Theses Bank of Capes. Using for this words – taken from our key themes: training, multiplicative conceptual field and early years.
Keywords: Continuous Training; Multiplicative conceptual field; Early years